2005
DOI: 10.1590/s1806-37132005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose em município de porte médio do Sudeste do Brasil: indicadores de morbidade e mortalidade, de 1985 a 2003

Abstract: INTRODUÇÃO: A tuberculose é uma doença ligada à pobreza, má distribuição de renda, urbanização, epidemia da síndrome da imunodeficiência adquirida, e multirresistência. OBJETIVO: Analisar indicadores de morbidade e mortalidade por tuberculose de São José do Rio Preto, entre 1985 e 2003, comparados com os do Estado de São Paulo e Brasil. Verificar a relação entre risco de ocorrência da doença e níveis socioeconômicos. MÉTODO: Sistemas de informações utilizados: Mortalidade (SIM), Notificação de Tuberculose (Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0
28

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 3 publications
5
19
0
28
Order By: Relevance
“…In 2002, the ST coverage among non-TB/HIV co-infected individuals was below 20% but reached 59% in that same year (13) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, the ST coverage among non-TB/HIV co-infected individuals was below 20% but reached 59% in that same year (13) .…”
Section: Discussionmentioning
confidence: 99%
“…In 1998, the coverage of the strategy was 3.1%, increasing to 62% in 2004. (6) The number of new cases of pulmonary TB with positive sputum smear microscopy results at diagnosis in relation to treatment noncompliance, cure, death, and detection, between 1998 and 2003, indicate decreases in the rates of treatment noncompliance and case detection, as well as increases in cure rates and mortality rates (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…(3) In 1998, the DOTS strategy was proposed, incorporated into the National Tuberculosis Control Plan, (4) and gradually implemented in Brazilian cities as a strategy within the Unified Health System, encouraging the identification and treatment of new cases by granting benefits upon the signatories of a statement of compliance. (5) The city of São José do Rio Preto (SJRP), with a population of 406,827 inhabitants, (6) is located in the northwest region of the state of São Paulo, which is characterized as a regional center, the headquarters of the 8th administrative region (comprising 96 municipalities), and an area of influence that reaches part of the states of Minas Gerais, Mato Grosso, and Mato Grosso do Sul.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to ST has been analyzed by many researchers (1)(2)(3)13,15,21) since the implementation of the DOTS in the state of São Paulo. Many of these researchers concluded that the strategy increases adherence rates and diminishes abandonment.…”
Section: Rev Esc Enfermmentioning
confidence: 99%